Autonomous Mobile Pharmacy (AMPharmy): Identification of hospital objects and their respective positions - Fabricio, Felipe; Oliveira, André Schneider de; Teixeira, Marco A. S.; Günther, Gustavo (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2023: Anais do XV Simpósio Brasileiro de Robótica e XX Simpósio Latino Americano de Robótica, 2023)
Robots are an increasing force in the daily lives of most people in the world, able to be used for the most different kind of purposes. In this project, the authors propose a medical robot, capable of delivering medicine to patients autonomously through an hospital, and simulate its performance through the CoppeliaSim software, by using computer vision and YOLOv8, state-of-art in object detection, to find specific landmarks through the simulated ambient. The aim of this project is for the robot to be able to navigate the hospital environment autonomously, identifying points of interest and interacting with them. For this, it is first necessary to identify these objectives and the robot’s distance. This work focuses on identifying hospital objects and capturing the distance between objects and the robot.